Don't just "sign"-- communicate! : a student's guide to mastering ASL grammar - Jay, Michelle (Los Angeles, CA : Judea Media, 2011)
This text methodically takes readers through the essentials of ASL grammar to prepare them to truly and effectively communicate in and understand ASL.
Includes bibliographical references (p. 149) and index.
Keywords: American Sign Language; American Sign Language